A note on the roughness measure of fuzzy sets - Pattaraintakorn, P.; Naruedomkul, K.; Palasit, K. (My University, 2009)
In this work, we study the roughness measure of fuzzy sets. New properties and roughness bounds for fuzzy set operations are established. Knowing these bounds of the operations results helps one to avoid unnecessary space in computation. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Fuzzy set theory; Rough set theory; Roughness measure